Background subtraction via colour coherence under varying illuminations. Issue 25 (1st December 2018) - Kim, Wonjun
Abstract : An illumination‐invariant method for background subtraction is presented. Inspired by the observation that the degree of dispersion in the colour space, which is computed from the local region of each frame, is not severely changed even with varying illuminations, To exploit the colour coherence as the features for formulating the background model is proposed. Experimental results on various benchmark databases show the efficiency and robustness of the proposed method compared to the previous approaches introduced in the literature.